Development of Power Converter Digital Control System Using Psim, Matlab/Simulink And Digital Signal Processor Stm32f407 - V. Talanov, M.; V. Karasev, A.; M. Talanov, V. (International Journal of Engineering and Technology, 2018)
At present, the development of digital control systems based on a microcontroller is carried out using a variety of modeling systems such as, for example, Matlab and PSIM. Modern programming technologies allow to combine Matlab and PSIM to perform simulations to take advantage of both modeling systems. The present market offers evaluation boards with a powerful microcontroller, which supports different peripheral units and data exchange protocols and allows connecting to a personal computer [1, 2]. This article deals with the development of the modeling method in which the control system based on the STM32F407 microcontroller will control the mathematical model of the developed converter. Â Â